DIAGNOSTIC CLASSIFICATION OF MENTAL HEALTH AND DEVELOPMENTAL DISORDERS OF INFANCY AND EARLY CHILDHOOD DC:0–5: SELECTIVE REVIEWS FROM A NEW NOSOLOGY FOR EARLY CHILDHOOD PSYCHOPATHOLOGY. Issue 5 (29th August 2016) - Zeanah, Charles H.; Carter, Alice S.; Cohen, Julie; Egger, Helen; Gleason, Mary Margaret; Keren, Miri; Lieberman, Alicia; Mulrooney, Kathleen; Oser, Cindy
ABSTRACT: The Diagnostic Classification of Mental Health and Developmental Disorders of Infancy and Early Childhood: Revised Edition ( DC:0–5 ; ZERO TO THREE) is scheduled to be published in 2016. The articles in this section are selective reviews that have been undertaken as part of the process of refining and updating the nosology. They provide the rationales for new disorders, for disorders that had not been included previously in the Diagnostic Classification of Mental Health and Developmental Disorders of Infancy and Early Childhood: Revised Edition ( DC:0–3R ; ZERO TO THREE, 2005), and for changes in how certain types of disorders are conceptualized.